2002
DOI: 10.1016/s0020-7683(02)00241-x
|View full text |Cite
|
Sign up to set email alerts
|

The structural performance of near-optimized truss core panels

Abstract: Theoretical studies have indicated that truss core panels with a tetragonal topology support bending and compression loads at lower weight than competing concepts. The goal of this study is to validate this prediction by implementing an experimental protocol that probes the key mechanical characteristics while addressing node eccentricity and structural robustness. For this purpose, panels have been fabricated from a beryllium-copper alloy using a rapid prototyping approach and investment casting. Measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
142
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 273 publications
(145 citation statements)
references
References 10 publications
2
142
0
1
Order By: Relevance
“…Using the upper bound of measured strut modulus E s = 100 GPa (close to the 105 GPa lower bound for bulk Ti-6Al-4V, Table III), Eq. [2] predicts stiffness values for panels A and B (with 13.1 and 16.0 pct relative densities) of 2.7 and 3.2 GPa, respectively, as compared with measured values of 1.2 and 2.9 GPa (Table III), respectively. Deshpande et al [6] also found that Eq.…”
Section: Panel Compressive Propertiesmentioning
confidence: 77%
See 3 more Smart Citations
“…Using the upper bound of measured strut modulus E s = 100 GPa (close to the 105 GPa lower bound for bulk Ti-6Al-4V, Table III), Eq. [2] predicts stiffness values for panels A and B (with 13.1 and 16.0 pct relative densities) of 2.7 and 3.2 GPa, respectively, as compared with measured values of 1.2 and 2.9 GPa (Table III), respectively. Deshpande et al [6] also found that Eq.…”
Section: Panel Compressive Propertiesmentioning
confidence: 77%
“…Deshpande et al [6] also found that Eq. [2] overpredicted the modulus of a cast aluminum alloy LBS panel, which they attributed to the ''bedding-in'' of the struts into the nodes during the initial stages of deformation. Additionally, the present panels exhibit nodes that are thicker than in the model, as well as additional face struts, which both reduce their stiffness as compared with Eq.…”
Section: Panel Compressive Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Lattice structures such as corrugations, honeycombs and trusses have high quasi-static stiffness and strength [8][9] and high dynamic strength [10][11]: they show potential as the cores of sandwich plates. However, experimental studies are needed in order to demonstrate explicitly their performance advantage in terms of underwater blast resistance.…”
Section: Introductionmentioning
confidence: 99%